Multifunctional composite modified straw fiber with high water absorption and growth promotion and matrix block
By modifying the preparation method of straw fiber, the problems of poor hydrophilicity and unstable size of straw substrate blocks in rice seedling cultivation were solved, and straw fiber substrate blocks with high water absorption and stable structure were realized, which improved the growth and germination rate of seedlings.
Patent Information
- Application Number
- CN202512042215.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-31
- Publication Date
- 2026-03-20
AI Technical Summary
Existing straw substrate blocks have problems such as poor hydrophilicity, small porosity, unstable size, uneven water absorption, and increased microenvironment temperature during rice seedling cultivation, which affect seedling growth and germination rate.
Highly absorbent composite modified straw fibers are used to prepare highly absorbent and dimensionally stable straw fibers through the synergistic effect of eutectic solvents, metal salts and precipitation promoters, combined with hydrothermal treatment and mechanical decomposition. These fibers are then used to prepare single-layer or multi-layer matrix blocks, thereby improving the hydrophilicity and structural stability of the straw fibers.
It significantly improves the water absorption and dimensional stability of straw fiber, enhances the overall quality and stress resistance of seedlings, solves the problems of uneven water absorption and increased microenvironment temperature in traditional methods, and promotes uniform growth and germination rate of seedlings.
Smart Images

Figure CN121700702A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the fields of biomass fiber modification, functional materials, and rice seedling substrate technology, and in particular to a composite modified straw fiber and substrate block with high water absorption and multifunctional growth promotion. Background Technology
[0002] Traditional rice seedling raising using machine transplanting has long relied on a "plastic seedling tray + nutrient soil" model. This model faces significant challenges, including difficulty in obtaining soil, disposal of discarded seedling trays, and high costs. To address these issues, reports have emerged of using straw substrate blocks to replace plastic seedling trays. Straw substrate blocks are typically made from rice, corn, rapeseed, or other straws. Through fermentation and composting, "biological-mechanical" decomposition, fiber reconstruction, nutrient activation, and filtration molding, they are created as block or sheet-like substrate materials. These materials offer advantages such as a complete product structure, good water and air permeability, low salinity, balanced nutrients, and biodegradability. Seedlings raised using these blocks meet the standards for machine transplanting of rice, thus making them a viable alternative to traditional seedling soil in rice seedling raising and machine transplanting techniques.
[0003] The dissociation and reconstruction of straw fibers are indispensable steps in the preparation of substrate blocks. Chinese patent CN202110436082.4 discloses a method for dissociating the S2 layer of the secondary wall of plant fibers, which can expose the high cellulose content of the S2 layer and increase its specific surface area while preserving its original spatial structure. This invention utilizes H2O2 solution and NaOH solution to impregnate plant samples to degrade hemicellulose and lignin. Although the dissociation of the plant fiber S2 layer solves the problems of low surface active sites and large molecular barriers, the chemical dissociation method brings more pollution reprocessing problems, and the subsequent application of residual chemical reagents is detrimental to crop physiological development. Patent CN201811336824.0 discloses a multi-layer straw substrate for dry-land rice seedling trays. This invention involves mixing crop straw fibers with manure water for fermentation to obtain decomposed straw fibers. After extrusion and puffing, the cellulose inside the long-fiber straw is disintegrated and assembled. However, the source of manure elements and microbial composition in this method is uncertain, resulting in low uniformity of the performance of the prepared multi-layer straw matrix. In the subsequent improvement of this technology (CN201910978528.9), straw is first mixed with active microbial agents and fermented to obtain plastic fibrous straw fibers. Then, it is compounded with other beneficial conditioning agents and subjected to pulping, homogenization, and negative pressure adsorption to obtain straw seedling substrate blocks. Its dimensional stability, water retention and nutrient activity are greatly improved. Although the straw substrate blocks prepared by this improved method can meet the requirements of rice seedling raising and machine transplanting, it still has disadvantages such as long straw fiber pretreatment process cycle (6 days), high material loss rate and single functional effect. Furthermore, during the promotion in different application areas, it was found that the straw substrate blocks still have problems such as poor hydrophilicity and small porosity. In addition, the surface size regularity of the substrate blocks prepared by this method is poor. During the automated seedling raising process, the surface moisture of the substrate blocks is prone to loss. This leads to problems such as insufficient water absorption by rice seeds during the darkening period after sowing, resulting in local water shortage and failure to germinate. Uneven water absorption also causes local loosening or compaction of the substrate blocks, resulting in uneven emergence of seedlings. In addition, when the moisture content of some straw is at the critical threshold suitable for microbial fermentation, fermentation of the microenvironment is easily formed, which leads to an increase in the internal temperature of the darkened stacked products, reducing the root vitality and germination activity of rice seeds.
[0004] More seriously, during the pretreatment stage of existing substrate block preparation, it was found that lignin produced during the depolymerization process of lignocellulose easily self-condenses and deposits on the fiber surface, resulting in the ineffective exposure of hydrophilic groups on the straw fiber surface, thus reducing the fiber's water absorption. Furthermore, the aggregated phenolic compounds are prone to releasing allelochemicals that inhibit seed germination during the subsequent seedling cultivation process, particularly during water management in the seedling trays. Therefore, based on these factors, improving the quality stability, water absorption characteristics, quality, and functional diversity of straw substrate blocks to adapt them for large-scale application and promotion has become a pressing technical challenge in this field. Summary of the Invention
[0005] To address the aforementioned issues, this application provides a highly absorbent, multifunctional composite modified straw fiber, and utilizes the straw fiber filaments prepared by this method to develop single-layer or multi-layer structured substrate blocks, thereby improving the dimensional stability, water absorption, and matching efficiency of automated seedling raising and the quality of seedlings in the population.
[0006] The method described in this application can separate fibers with high solid content without generating wastewater; it also has a short pretreatment cycle for straw lignocellulose dismantling (within 24 hours), low operating energy consumption, strong fiber hydrophilicity, high seedling quality and strong seedling index, and strong crop growth resistance. At the same time, it reduces the production of phenolic acid allelochemicals and promotes seed growth and development.
[0007] Specifically, the technical solution provided in this application is as follows: First, this application provides a highly absorbent, growth-promoting composite modified straw fiber, which is prepared by the following method: S1: Inject the dissociation aid solution into the reaction vessel, add the metal salt to the reaction system at 80℃, stir and keep warm for 30 minutes, and after thorough mixing, obtain the dissociation aid system; The above-mentioned dissociation aid is prepared by the following method: first, choline chloride and formic acid are mixed evenly at a molar ratio of 1:1 to obtain a eutectic solvent; the mixture is heated to a molten state (about 80°C), and then water preheated to 75~80°C is added. Eugenol is then added, and the mixture is stirred thoroughly to prepare a solution with a mass fraction of 0.1~0.5%; the preferred mass ratio of eugenol to eutectic solvent is 1:2. The aforementioned metal salt is obtained by mixing zinc salt and cerium salt in a molar mass ratio of (0~1):1, with a further preferred molar mass ratio of zinc salt to cerium salt of (0.5~1):1; the amount of metal salt added is preferably 0.01~0.1% of the dry matter of the straw section; preferably, the zinc salt is zinc chloride; and the cerium salt is one or more of cerium chloride, cerium nitrate, or cerium sulfate. In this step, eugenol, as a highly nucleophilic phenolic compound, can induce binding with unstable intermediates (such as carbocations) in lignin depolymerization products to form stable covalent bonds, thereby inhibiting the condensation reaction between lignin molecules, reducing the redeposition of lignin on the surface of straw fibers, and thus improving the hydrophilic properties of the fibers.
[0008] S2: After the S1 dissociation promoter system cools to room temperature, add the straw segments, mix the materials evenly and add the sedimentation promoter, and soak at room temperature for 3~12 h to obtain high-moisture pretreated straw segments with a moisture content of 75~95%. The precipitation promoter mentioned above is at least one of urea or ammonia (concentration 25%-28%); the preferred amount of precipitation promoter added is 0.1-0.5% of the dry matter weight of the straw section; The mass of the added dissociation aid is 0.1-0.5% of the dry matter of the straw segments; Overall, the preferred mass ratio of straw segments, dissociation aid, metal salt, and precipitation promoter is 100:(0.1~0.5):(0.01~0.1):(0.1~0.5). S3: The high-moisture pretreated straw segments obtained in step S2 are placed in a steam treatment at 100~120℃ for 30~120 min (hydrothermal environment) to obtain high water-absorbing straw segments with a moisture content of 80~85%; the surface hydrophilic groups of the high water-absorbing straw segments after this step are significantly improved, and they exhibit extremely high water absorption characteristics in subsequent treatment steps.
[0009] This step utilizes a hydrothermal environment to further promote the homogenization and formation of micro / nano cerium oxide / zinc oxide within the cell cavities of straw fibers, improving the adhesion and accessibility of the nanocatalyst on the fiber surface and inner structure. The enzyme-like activity of the micro / nano cerium oxide / zinc oxide efficiently disrupts lignin-carbohydrate complexes (LCCs), significantly reducing resistance to mass transport and enhancing the thermocatalytic dissociation and fiber splitting effects, thereby strengthening the fiber's self-interlacing and anchoring capabilities. Furthermore, the self-pressurized steam temperature in the hydrothermal environment is controlled at 100℃-120℃ (lower than the conventional 180℃-220℃ temperature for straw hydrothermal reactions), allowing the vaporization and volatilization of weak acids generated in the mixture to enter the supramolecular structure of the straw fiber cell walls for catalysis and enhancing the degree of steam dissociation, further achieving energy conservation and emission reduction.
[0010] S4: Add 0.1% to 0.3% of citric acid (preferably 5% concentration) to the highly absorbent straw segments obtained in S3. After mixing evenly, mechanically decompose and separate the fibers using a twin-screw extruder or a single-axis tearing and spinning machine to prepare composite modified and activated straw fiber SF with a moisture content of 50% to 55%, good flexibility, high water absorption, and growth promotion. At the same time, a dark brown liquid with high activity containing straw-derived macromolecular structure is produced simultaneously during the extrusion or tearing process.
[0011] The twin-screw extruder or single-shaft tearing and spinning machine used in this step are conventional machines in this field, such as the twin-screw extruder produced by Jiangsu Jinwo Machinery Co., Ltd., and the single-shaft tearing and spinning machine produced by Zhucheng Hongyu Environmental Protection Technology Co., Ltd. Their processing functions combine tearing, loosening, kneading, and fiberization. Furthermore, after loosening, the minerals and organic nutrients inside the straw fibers are more easily released. The extrusion or tearing process can further effectively reduce the adhesion of lignin to the surface of the straw fibers, promote the exposure of hydrophilic groups on the surface, and improve its hydrophilicity, resulting in better water absorption in subsequent use.
[0012] Preferably, the straw used in the above steps includes at least one of agricultural and forestry waste straws such as rice, wheat, corn, cotton stalks, bamboo, reeds, sorghum, hemp stalks, and sugarcane bagasse.
[0013] In one embodiment of this application, the hydrothermal environment of step S3 refers to uniformly placing the high-humidity pretreated straw from step S2 into several layers (such as 1, 2, 3, 4 layers, preferably 2-3 layers) of stainless steel steaming plates, and then placing it in a cooking tank for hydrothermal treatment. In one embodiment of this application, the stainless steel steaming plates used have circular holes with a diameter of 0.3-0.5 cm and a spacing of 3 cm between the holes. The multi-layered steaming plate structure can improve the mass transfer efficiency and rate of steam, and during operation, this multi-layered steaming plate structure also has the advantage of generating micro-nano-scale bubbles. The shear force generated by the expansion of the bubbles has the function of tearing the middle lamellae connecting the cellulose microfibrils, loosening the originally tightly bound fiber bundles, and further improving the catalytic effect and dissociation degree of the straw fibers. The aforementioned bubble effect mainly refers to the fact that when the water in the cooking tank is heated and vaporized during hydrothermal treatment, steam is generated. The steam can flow between the multiple layers through the circular holes of the steaming plates, so that the steam can be distributed more evenly throughout the entire layer space, rather than concentrated in a certain area. When steam passes through the perforated stainless steel shelf, the presence of pores obstructs its passage, causing localized changes in steam pressure. Near the pores, the steam pressure is relatively high. When this pressure reaches a certain level, it overcomes the surface tension of the surrounding liquid, forming tiny bubbles. These bubbles are initially small, at the micro-nano scale. As the hydrothermal treatment continues, steam is continuously generated and enters the bubbles, further increasing the internal pressure and causing them to expand. During this expansion, strong shear forces are generated. These shear forces act directly on the intercellular layer connecting the straw cellulose microfibrils (the intercellular layer is the structure connecting adjacent cell walls, holding the originally tightly bound fiber bundles together). The shear force generated by the bubble expansion can disrupt the structure of the intercellular layer, tearing it apart and causing the originally tightly bound fiber bundles to loosen.
[0014] Secondly, this application provides a homogenized single-layer matrix block prepared from the above-mentioned composite modified activated straw fiber SF: the matrix block is prepared by suction filtration molding method using the composite modified activated straw fiber SF obtained in step S4 as raw material.
[0015] The suction filtration molding method used in this step is a conventional method in the field, such as the method disclosed in patent CN201910978528.9. In the specific preparation process, a single-station reciprocating molding machine is used for suction filtration molding under negative pressure (-0.01 MPa), and a vacuum pump maintains a negative pressure of -0.1 to -0.01 MPa in the mold cavity. The product is then dried in a drying tunnel at 45°C. Compared to the substrate blocks prepared by that patent (CN201910978528.9), the substrate blocks prepared using composite modified activated straw fiber SF in this application significantly improve the surface water absorption rate during seedling production.
[0016] Third, this application also provides a multi-layer matrix block, wherein the upper layer is the composite modified activated straw fiber SF (S-SF) obtained in step S4 above, the lower layer is straw fiber SF (U-SF) sprayed with a highly active dark brown liquid containing straw-derived macromolecular structures, and the middle layer is a material composition of S-SF and U-SF fully mixed in a 1:1 mass ratio (M-SF); that is, S-SF, M-SF and U-SF are arranged by fiber self-interlacing to form a stable skeleton network structure, and then dry-pressed by hot press to obtain a multi-layer matrix block. In one embodiment of this application, the fiber layup thickness of S-SF, M-SF and U-SF is the same, the total thickness of the pressed multi-layer matrix block is about 1.0 cm, and the bulk density is 0.1~0.13 g / cm³. 3 .
[0017] Preferably, during the preparation of U-SF fiber, the amount of the dark brown liquid containing the highly active macromolecular structure of straw source sprayed is 5% (ml / mg) of the volume mass ratio of the composite modified and activated straw fiber SF.
[0018] Preferably, the hot press temperature is 100-120℃, the pressure is 10 MPa, and the holding time is 2-3 min.
[0019] The multi-layered matrix block allows for various functional designs. The upper layer consists of composite modified and activated straw fibers (SF) with high surface hydrophilic groups, which not only have high water absorption and porosity but also create a matrix with good air permeability, promoting seed germination. The lower layer of straw fibers is surface-treated with a highly active dark brown liquid containing straw-derived macromolecular structures. During hot pressing, the lignin-rich dark brown liquid softens the fibers, providing a thickening effect. Through intermolecular forces, the dispersed straw fibers are formed into a composite adhesive system. Furthermore, during fiber disintegration, a small amount of cellulose and hemicellulose are released. The sugars produced during cellulose decomposition remain in a dark brown liquid during extrusion or tearing. When sprayed onto the fiber surface, the low-molecular-weight reducing sugars, such as xylose and glucose, can fill the spaces between lignin (polyphenol polymer) molecules, reducing their local concentration. Simultaneously, the hygroscopic nature of the sugars increases the system viscosity, slowing down the lignin phase separation and promoting more uniform distribution. This structure enhances the overall tensile and compressive strength of the multilayer matrix block and significantly improves the product's shape regularity, facilitating subsequent packaging and long-term storage, and improving its molding quality. Furthermore, the matrix blocks prepared by this method have a smoother surface and smoother edges, making them more suitable for automated production lines.
[0020] Compared with the prior art, the beneficial effects of the present invention are reflected in: 1. The introduction of the three-component compound dissociation aid in the reaction system of this application can effectively promote the dissociation effect of the catalytic system, reduce the redeposition of depolymerized lignin on the fiber surface during the dissociation of straw fibers, effectively improve the hydrophilicity of the straw fiber surface due to the weakening of the hydrophobic lignin coating, and improve the quality of the finished straw fiber.
[0021] 2. The micro / nano cerium oxide generated in situ in the reaction system in this application possesses nanoenzyme properties. During the catalytic dissociation of straw fibers, the fluorite structure of cerium oxide endows it with a unique Ce³⁺ / Ce⁻ ratio. 4 The redox cycle capacity is enhanced; under steam heating conditions, the oxygen vacancies in CeO2 further promote redox reactions, accelerating the directional depolymerization of straw macromolecules (such as lignin), reducing lignin redeposition on the straw fiber surface, and thus lowering energy consumption in the subsequent mechanical debonding and fiber separation process, relatively improving fiber dissociation efficiency. Furthermore, the dissociated straw fiber surface contains cerium-zinc-silicon fertilizer and increased mineral element activity, exhibiting significant growth-promoting and stress-resistance effects in rice seedling cultivation, improving the growth and development of rice seedlings.
[0022] 3. The water absorption characteristics of the composite modified activated straw fiber SF prepared in this application are significantly improved compared with those of bio-fermented straw fiber. The water absorption rate of the straw fiber treated in this application reaches 578%, which is 4 times higher than that of current bio-fermentation (water absorption rate of about 137%). The substrate blocks prepared using composite modified activated straw fiber SF have strong water absorption. By optimizing the physical structure, the efficiency of automated seedling raising is effectively improved. During the darkening period, the moisture content of the substrate blocks is well uniform, resulting in high seedling quality. This effectively solves the risk of "seedling burning" that exists in substrate blocks prepared by traditional methods, and helps to address the challenges of climate change. At the same time, the nano-oxides are uniformly loaded in the straw fiber network, and the prepared substrate blocks easily form a gradient concentration field during the seedling raising period, which is conducive to inducing targeted growth of rice roots. In addition, after the straw fiber is torn and split, the conversion of endogenous nutrients and other elements in the straw into forms that can be absorbed by plants is significantly increased, which improves the overall growth and stress resistance of seedlings.
[0023] 4. The multi-layered substrate blocks prepared by this method through dry fiber self-interlacing and lamination have high flatness on the top and bottom surfaces and around the edges, effectively solving the problems of uneven surface of existing substrate blocks and poor compatibility with plastic seedling trays, resulting in unbalanced water absorption and low uniformity of rice seed distribution.
[0024] 5. This method produces a dark brown liquid with high activity from straw-derived macromolecular structures while preparing straw fiber. Its components include phenolic compounds, polysaccharides, amino acids, and cerium and zinc nanozymes. It can also be used as a foliar spray or soil conditioner to improve crop resistance and soil structure. Attached Figure Description
[0025] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments.
[0026] Figure 1 The composite modified straw fiber prepared in Example 2.
[0027] Figure 2 Comparison of surface colors of straw fibers in Example 4.
[0028] Figure 3 Example 6: Schematic diagram of a multilayer matrix block.
[0029] Figure 4 Performance testing: Dynamic changes in water absorption rate of straw substrate blocks over 90 seconds under ambient temperature conditions.
[0030] Figure 5 The dynamic change of the surface contact angle of the performance test matrix block over time.
[0031] Figure 6 Demonstration of dynamic changes in moisture absorption on the surface of the performance test substrate block.
[0032] Figure 7 The effect of performance testing substrate blocks on rice root tangling.
[0033] Figure 8 The root development ability of seedlings grown in the performance test substrate block was tested.
[0034] Figure 9 Performance testing revealed that the main phenolic acids in the highly active, dark brown liquid derived from straw were macromolecular structures. Detailed Implementation
[0035] The following embodiments are only used to more clearly illustrate the technical solutions of the present invention, and should not be construed as limiting the scope of protection of the present invention. Unless otherwise defined, the technical or scientific terms used in this invention should have the ordinary meaning understood by those skilled in the art. The instruments, equipment, and reagents used in this invention are all commercially available.
[0036] Example 1: Preparation of highly absorbent, multifunctional composite modified straw fiber
[0037] The steps for preparing highly absorbent, multifunctional composite modified straw fiber in this embodiment are as follows: S1: Mix choline chloride and formic acid in a molar ratio of 1:1 to obtain a eutectic solvent; then heat to 80°C until melted, add to water preheated to 75~80°C, then add eugenol, the mass ratio of eugenol to eutectic solvent is 1:2; stir thoroughly to prepare a dissociation aid with a mass fraction of 0.5%; The dissociation aid was injected into the reaction vessel, and the metal salt cerium chloride was added to the reaction system at 80°C. The mixture was stirred and kept warm for 30 minutes. After thorough mixing, the dissociation aid system was obtained and allowed to cool naturally to room temperature. S2: Add 3-5 cm long rice straw segments to the dissociation promoter system in S1 that has been cooled to room temperature, mix the materials evenly, use urea as a precipitation promoter, soak and age at room temperature for 12 h to obtain high-moisture pretreated straw with a moisture content controlled at 95%; In this embodiment, the mass ratio of straw segments (by dry matter), dissociation aid, metal salt, and urea is 100:0.5:0.1:0.5.
[0038] In actual operation, the mass ratio of straw segments, dissociation aid, metal salt, and urea can also be within the range of 100:(0.1~0.5):(0.01~0.1):(0.1~0.5), which can achieve the purpose of the invention.
[0039] Besides rice straw, straw can also be one or more of the following agricultural and forestry waste straws: wheat straw, corn straw, cotton straw, bamboo straw, reed straw, sorghum straw, hemp straw, sugarcane bagasse, etc.
[0040] S3: Add water to the digester (purchased from Shandong Guiguan Machinery Co., Ltd., pressure test pressure 1.02 MPa), place stainless steel steaming plates inside, and evenly place the high-moisture pretreated straw prepared in step S3 onto the steaming plates. In this embodiment, the digester has two layers of stainless steel steaming plates (in specific implementations, 1-4 layers of steaming plates can be set according to the actual situation of the digester). Then cover the digester with the lid. Steam treatment is carried out at 120℃ hydrothermal conditions for 120 min to obtain modified straw segments with high water absorption capacity.
[0041] In this embodiment, the stainless steel steaming plate used is a stainless steel plate with round holes of 0.3 cm in diameter and a spacing of about 3 cm between the round holes.
[0042] S4: Spray a 5% citric acid solution onto the modified straw segments with high water absorption obtained in S3. The mass of the added citric acid is 0.1% of the dry mass of the straw segments. Mix the materials thoroughly and age for 60 min. Then, use a twin-screw extruder (model 80, main power 45 kW, screw diameter 75 mm, screw speed 400 rpm, Jiangsu Jinwo Machinery Co., Ltd.) to mechanically decompose and separate the fibers of the straw segments to prepare composite modified and activated straw fiber SF with good flexibility, high water absorption and growth promotion. During the straw segment extrusion process, collect a dark brown liquid with high activity of straw-derived macromolecular structure.
[0043] Example 2 In this embodiment, the preparation steps of the highly absorbent and multifunctional composite modified straw fiber are as follows: S1: Mix choline chloride and formic acid in a molar ratio of 1:1 to obtain a eutectic solvent. Then heat the solvent to 80°C to melt it. Add the solvent to water at 75-80°C and then add eugenol (the mass ratio of eugenol to the eutectic solvent is 1:2). Stir thoroughly to prepare a dissociation aid solution with a mass fraction of 0.1%. The dissociation aid solution was injected into the reaction vessel, and a metal salt (zinc chloride and cerium nitrate were mixed at a molar mass ratio of 1:2) was added to the reaction system at 80°C. The mixture was stirred and kept at the temperature for 30 min. After thorough mixing, the dissociation aid system was obtained. S2: Add 3-5 cm long wheat straw segments to the dissociation promoter system in S1, mix the materials evenly, use ammonia water (an aqueous solution containing 25% ammonia by mass) as a precipitation promoter, soak and age at room temperature for 3 hours to obtain high-moisture pretreated straw with a moisture content controlled at 75%; The mass ratio of straw segments, dissociation aid, metal salt, and ammonia water is 100:0.1:0.01:0.1.
[0044] S3: The high-humidity pretreated straw segments from S2 are placed in a cooking tank with two layers of stainless steel steam plates (same as in Example 1), and steamed at 120°C for 30 minutes in a hydrothermal environment to obtain modified straw segments with high water absorption capacity.
[0045] S4: Spray a 5% citric acid solution (0.3% of the dry weight of the straw segments) onto the highly absorbent straw segments obtained in S3. Thoroughly mix the material and allow it to age for 60 minutes. Then, use a single-shaft tearing and spinning machine (model ZSLJ-220, spiral diameter Φ220 mm, production capacity 1 t / d, spindle speed 80-120 r / min, Zhucheng Hongyu Environmental Protection Technology Co., Ltd.) to mechanically decompose and separate the straw segments into fibers, producing a composite modified straw fiber SF with good flexibility, high water absorption, and growth promotion properties. A physical image is shown below. Figure 1 As shown, Figure 1 In this example, A and B are both modified straw fibers SF prepared in this embodiment. During the straw segment tearing process, a dark brown liquid with high activity containing straw-derived macromolecular structures is collected simultaneously.
[0046] Example 3 In this embodiment, the preparation steps of the highly absorbent and multifunctional composite modified straw fiber are as follows: S1: Mix choline chloride and formic acid in a molar ratio of 1:1 to obtain a eutectic solvent; then heat to 80°C to melt, add to water at 75~80°C, then add eugenol (mass ratio of eugenol to eutectic solvent is 1:2), and stir thoroughly to prepare a dissociation aid solution with a mass fraction of 0.5%. The dissociation aid solution was injected into the reaction vessel, and a metal salt (zinc chloride and cerium nitrate were mixed at a molar mass ratio of 1:2) was added to the reaction system at 80°C. The mixture was stirred and kept at the temperature for 30 min. After thorough mixing, the dissociation aid system was obtained. S2: Add 3-5 cm long rice straw segments to the dissociation promoter system in S1, mix the materials evenly, use urea as a precipitation promoter, soak and age at room temperature for 6 hours to obtain high-moisture pretreated straw with a moisture content controlled at 85%; The mass ratio of straw segments, dissociation aid, metal salt, and urea is 100:0.3:0.05:0.5.
[0047] S3: The high-humidity pretreated straw segments from S2 are placed in a cooking tank with two layers of stainless steel steam plates (same as in Example 1), and steamed at 120°C for 60 min in a hydrothermal environment to obtain modified straw segments with high water absorption capacity.
[0048] S4: Spray a 5% citric acid solution onto the highly absorbent straw segments obtained in S3. The mass of the added citric acid is 0.2% of the dry mass of the straw segments. Mix the materials thoroughly and age for 60 minutes. Then, use a uniaxial tearing and spinning machine to mechanically decompose and separate the straw segments into fibers to prepare composite modified straw fiber SF, which has good flexibility, high water absorption, and promotes growth. During the tearing process of the straw segments, collect a dark brown liquid containing highly active macromolecular structures from straw.
[0049] Comparative Example 1 The steps for preparing the highly absorbent, multifunctional composite modified straw fiber in this embodiment are the same as in Example 1, except that no metal salt is added in step S1, and a dark brown liquid with highly active straw fiber SF and straw-derived macromolecular structure is obtained.
[0050] Comparative Example 2 The steps for preparing highly absorbent and multifunctional composite modified straw fiber in this embodiment are the same as in Example 2, except that no metal salt is added in step S1, and straw fiber SF and a dark brown liquid with highly active straw-derived macromolecular structure are obtained.
[0051] Comparative Example 3 The steps for preparing the highly absorbent, multifunctional composite modified straw fiber in this embodiment are the same as in Example 3, except that no metal salt is added in step S1 to obtain straw fiber SF and a dark brown liquid with highly active straw-derived macromolecular structure.
[0052] The main physicochemical properties of the straw fibers prepared in Examples 1-3 and Comparative Examples 1-3 are shown in Table 1: Table 1. Test results of the main physicochemical properties of straw fibers prepared in Examples 1-3 and Comparative Examples 1-3
[0053] The testing methods for the cellulose, hemicellulose, and lignin content of the prepared straw fiber are referenced in: Ma Huanhuan, Application of Amino Acid Ionic Liquids in Straw Resource Utilization [D], Master's Thesis, Jiangnan University, 2022. The methods disclosed herein are used for detection.
[0054] The test data in Table 1 above show that the straw fibers prepared using Examples 1-3 of this invention have a relatively high cellulose content, while the comparative examples have a lower cellulose content. Overall, the cellulose content is 3.89-6.39% higher than that of the comparative examples; while the hemicellulose and lignin contents are 2.62-8.72% and 4.62-8.65% lower, respectively, than those of the comparative examples. This indicates that the addition of zinc and cerium salts as dissociation promoters in the technical solutions of the examples can efficiently remove or depolymerize hemicellulose and lignin in the straw segments, thereby effectively retaining the cellulose components and improving the performance of subsequent straw-molded agricultural products. Furthermore, the composition of this structural component directly affects the physical properties of the fiber, such as strength and flexibility. The relative reduction in hemicellulose and lignin content helps improve the dispersibility and processability of the fiber.
[0055] Furthermore, the test results in Table 1 show that the ammonium nitrogen and nitrate nitrogen contents of the straw fibers prepared in Examples 1-3 are all higher than those in the corresponding Comparative Examples 1-3. Compared with Comparative Example 1, Example 1 introduced the metal salt cerium chloride during the pretreatment of straw segments. The addition of cerium salt, after the addition of a precipitation promoter, can form micro- and nano-cerium oxides in the cell cavities of straw segments. These oxides have enzyme-like effects, which can promote the breaking of molecular chains of the three elements in straw segments, disrupt the straw cell structure, and thus improve the conversion and release of relatively available nitrogen in the straw material system. Moreover, the straw fibers formed by this technical solution may act as attachment sites for available nitrogen, thereby reducing nitrogen loss.
[0056] To further verify the effect of dissociation aids on the depolymerization and redeposition of lignin within straw segments in the dissociation aid system, subsequent experiments were conducted.
[0057] Example 4 This embodiment uses Example 3 as the baseline for this experimental group: A: In step S1, no dissociation aid (choline chloride, formic acid or eugenol) is introduced, and then high-moisture pretreated straw is obtained; the straw fibers obtained from the high-moisture pretreated straw obtained in step S2 are naturally air-dried after squeezing out the water to obtain group A fibers. B: In step S1, no dissociation promoter system is introduced. Rice straw segments are directly added to water, and the other treatments are the same as in Example 3. The materials are mixed evenly, and then high-moisture pretreated straw is obtained. The high-moisture pretreated straw obtained in step S2 is squeezed to remove water and the resulting straw fibers are air-dried to obtain group B fibers. The fiber from the reference “Yong Cheng, et al. Effect of straw fiber size on drying and water absorption rate of seedling substrate blocks [J]. Chinese Agricultural Science Bulletin, 2024, 40(15): 143-150” was used as a comparison (hereinafter referred to as “bio-fermentation method”).
[0058] Comparing the straw fibers obtained in Examples 3 and 4 (Groups A and B) and Comparative Example 3 after natural air drying, and observing their surface color, it was found that the colors of the two groups of fibers obtained in Example 4 were significantly lighter than those reported in the reference report. Furthermore, the surface of the straw fibers obtained in Example 3 was cleaner, and the lignin redeposition phenomenon was significantly inhibited. Compared to Comparative Example 3, because Group A in Example 4 lacked the inhibitory effect of a dissociation aid, a large amount of the released lignin redeposited on the fiber surface, forming a dark brown covering layer, thus the color was slightly darker than that of Comparative Example 3. In contrast, the fibers in Group B obtained in Example 4 did not have a dissociation-promoting agent system added. During the steam treatment, the depolymerized lignin molecules, due to the large number of active groups, easily repolymerized on the fiber surface through condensation reactions in the system, forming a high molecular weight structure, resulting in a dark fiber surface color. Additionally, because the pretreatment process was in a heterogeneous state, the fiber surface color was uneven. (See the photograph for reference.) Figure 2 As shown, AE represents the straw fibers prepared according to Example 3, Comparative Example 3, Group A of Example 4, Group B of Example 4, and the reference.
[0059] To address the issue of slow water absorption rate encountered in the straw substrate block seedling production line (see the literature "Yong Cheng, et al. Effect of straw fiber size on drying and water absorption rate of seedling substrate blocks [J]. Chinese Agricultural Science Bulletin, 2024, 40(15): 143-150," where the shortest time for the substrate block to reach saturated moisture content is 61.5 min), the slow water absorption rate significantly affects the water absorption characteristics of the substrate block surface during the seedling production line process. This is because the lignin repolymerization deposition of the fiber surface in the early preparation method of the substrate block weakens the water absorption of the straw fiber, resulting in a relatively slow water absorption and water shortage on the substrate block surface during actual rice seedling production, especially in production line operations. Therefore, this embodiment measured the water absorption rate of the optimized straw fiber preparation method, and the results are shown in Table 2.
[0060] Table 2 clearly shows that the water absorption rates of Examples 3, 4A, 4B, and Comparative Example 3 are all significantly higher than the values in the reference. Example 3 achieved a water absorption rate of 578.03%, and even the relatively lower Example 4B reached 455.43%, while the reference only showed 137.14%. This difference clearly demonstrates that the steam pretreatment method used in this technology, compared to traditional bio-fermentation methods, can significantly improve the water absorption performance of straw fibers. Simultaneously, the introduction of the dissociation-promoting agent system also significantly increases the number of hydrophilic groups. This performance improvement is of great significance for applications requiring high water absorption, such as rice seedling substrates, where a higher water absorption rate means providing more sufficient moisture for rice seed germination, promoting seedling germination and root growth.
[0061] The above results indicate that the pretreatment process, whether using dissociation aids or adding zinc and cerium salts, effectively reduces lignin precipitation. Furthermore, introducing a dissociation promoter system during pretreatment more effectively addresses the phenomenon of lignin depolymerization and repolymerization depositing on the fiber surface, significantly improving the hydrophilicity of straw fibers. Analysis suggests that the addition of dissociation aids (choline chloride, formic acid, and eugenol) can assist in promoting the effective release of lignin and inhibiting its redeposition. Choline chloride forms a protective film on the fiber surface, hindering the adsorption and aggregation of lignin molecules; formic acid inhibits the self-assembly process of lignin molecules by adjusting the pH and ionic strength of the solution; and eugenol, a phenolic compound with high nucleophilic activity, can bind to unstable intermediates (such as carbocations) in lignin depolymerization products to form stable covalent bonds, thereby inhibiting the condensation reaction between lignin molecules. Metal salts can promote the dissociation of straw fibers and the depolymerization of lignin, but some deposition may occur due to the repolymerization of lignin. Overall, the pretreatment dissociation agent system formed by choline chloride / formic acid / eugenol / metal salt is beneficial to the dissociation of straw fibers.
[0062] Technological improvements are crucial for energy conservation, so the energy consumption in the straw fiber preparation process obtained by the above methods was compared simultaneously. Specific data are shown in Table 2.
[0063] Table 2 Comparison of energy consumption of straw fiber
[0064] Energy consumption was measured by referring to the literature: "Geng Bo, et al. Study on the effect of cellulase pretreatment on energy consumption and pulp properties of poplar pulping [J]. Forest Products Chemistry and Industry, 2025, 45(4): 97-104." As shown in Table 2, the straw fiber samples obtained by different pretreatment methods exhibit significant differences in energy consumption reduction (energy saving). Compared with the references, Examples 3, 4A, 4B, and Comparative Example 3 show outstanding energy saving, with energy savings of 45.35%, 34.78%, 17.07%, and 28.10%, respectively. Furthermore, compared with Example 4B, Examples 3, 4A, and Comparative Example 3 show energy savings of 13.31% to 34.11%. This indicates that compared with bio-fermentation pretreatment of straw, steam pretreatment of straw segments with the addition of a dissociation promoter system is an effective means to improve fiber dissociation and reduce energy consumption. The addition of dissociation aids and metal salts can further enhance the fiber dissociation effect, achieving even greater energy savings, and providing strong support for the optimization of related straw pretreatment processes and the efficient utilization of energy.
[0065] Example 5: Preparation of a single-layer matrix block Using the composite modified straw fiber SF obtained in Examples 1-3 as raw material, and referring to the patent "A method for preparing and applying a fully nutritious biodegradable straw seedling substrate block (CN201910978528.9)", single-layer straw substrate blocks (SSB) were prepared by suction filtration molding method. The single-layer substrate blocks prepared by the fibers in Examples 1-3 were labeled as WSSB-Ⅰ, WSSB-Ⅱ and WSSB-Ⅲ respectively.
[0066] Example 6: Preparation of multilayer matrix blocks
[0067] Using the composite modified straw fiber SF obtained in Examples 1-3 as raw material, a multi-layer discrete fiber stable skeleton network structure was formed through fiber self-interlacing and then pressed into multi-layer straw matrix blocks using a hot press. Specifically, the upper layer is the obtained composite modified activated straw fiber SF (S-SF); the lower layer is straw fiber SF (U-SF) sprayed with a dark brown liquid containing a high-activity macromolecular structure of straw, with a volume-to-mass ratio of 5% (ml / mg) of the sprayed dark brown liquid to straw SF; the middle layer is composed of material composed of S-SF and U-SF fully mixed in a 1:1 mass ratio (M-SF).
[0068] In this embodiment, when the surface of the straw fiber is treated with a dark brown liquid with high activity of straw-derived macromolecular structure, the moisture content of the material is controlled to be 45-55%. After uniform mixing and adhesion, it is aged at 60°C for 3 hours, pressure of 10 MPa, pre-cooled for 5 minutes, and then hot-pressed at 100-120°C, pressure of 10 MPa, and holding time of 3 minutes to obtain a dry self-woven multilayer straw matrix block. The multilayer matrix blocks prepared from the fibers in Examples 1-3 are sequentially labeled as DSSB-Ⅰ, DSSB-Ⅱ, and DSSB-Ⅲ. The schematic diagram of the prepared multilayer matrix block structure is shown below. Figure 3 As shown.
[0069] In this embodiment, the fiber layers of the upper, middle, and lower layers of the multi-layer matrix block have the same thickness, and the total thickness of the compressed multi-layer matrix block is controlled at 1.0 cm, with a bulk density controlled at 0.1~0.13 g / cm³. 3 .
[0070] Comparative Example 4 Using straw fibers obtained from Comparative Examples 1-3 as raw materials, single-layer matrix blocks were prepared according to the method in Example 5 to obtain comparative matrix blocks. The single-layer matrix blocks prepared based on the fibers of Comparative Examples 1-3 were labeled as CK-WSSB-Ⅰ, CK-WSSB-Ⅱ, and CK-WSSB-Ⅲ, respectively.
[0071] Comparative Example 5 Using straw fibers obtained in Comparative Examples 1-3 as raw materials, multilayer matrix blocks were prepared according to the method in Example 6 to obtain comparative matrix blocks. The multilayer matrix blocks prepared from the fibers in Examples 1-3 were labeled as CK-DSSB-Ⅰ, CK-DSSB-Ⅱ and CK-DSSB-Ⅲ, respectively.
[0072] Performance testing: The main performance test data of the matrix blocks prepared in Examples 5-6 and Comparative Examples 4-5 are shown in Table 3: Table 3. Main performance test results of straw substrate blocks prepared in Examples 5-6 and Comparative Examples 4-5
[0073] The tensile strength and flexural strength testing methods are as follows: The top and bottom surfaces of the substrate block must be flat and parallel to each other, and the long and short sides should be horizontal and perpendicular to each other. The length and width of the substrate block to be tested after cutting are 20 cm × 10 cm. The allowable error for the length of the substrate block is ±1 mm, and the allowable error for the width is ±0.5 mm, but the relative deviation of the width along the entire length of the substrate block should not exceed ±1 mm. Tensile tests are performed on the specimens along the length of the substrate block using a universal testing machine at a speed of 20 mm / min, with 6 parallel tests for each specimen to obtain its tensile strength. Bending tests are performed on the specimens using a universal testing machine at a speed of 50 mm / min, and the flexural strength at fracture is recorded.
[0074] Thickness uniformity test: The prepared substrate block was precisely cut into 10 cm × 10 cm square plates using a cutting tool. The square plates were placed flat on a glass plate, ensuring that the lower surface of the substrate block was tightly aligned with the upper surface of the glass and firmly fixed. Using a ruler with an accuracy of 0.1 mm, eight representative locations were selected on the substrate block, and the thickness was measured perpendicularly to the surface of the substrate block. The above measurement was repeated eight times for each treatment, and the measurement data were recorded each time. The standard error was calculated, and this standard error value was used to represent the thickness uniformity of the substrate block.
[0075] Water absorption rate test method: Cut the air-dried matrix block at room temperature into 10 cm × 10 cm samples, immerse them all in a water tank, maintain the same conditions, take them out within a specified time, remove the surface free water, weigh the wet sample, and calculate the water absorption rate based on the percentage of the weight of water absorbed by the original sample to the original weight.
[0076] As shown in Table 3, the matrix blocks prepared using straw fibers from Examples 1-3, whether single-layer or multi-layer structures, exhibit higher tensile and flexural strengths than those of Comparative Examples 1-3. Furthermore, the multi-layer matrix blocks obtained by dry-processing the self-interlacing of fibers to form a stable three-dimensional network skeleton structure, resulting in matrix blocks with higher tensile and flexural strengths than their corresponding single-layer counterparts, demonstrate that dry-process multi-layer self-interlacing hot-pressing is beneficial for improving the strength of the matrix blocks. The reason for this is that the dark brown liquid from straw-derived macromolecules, with its highly active macromolecular structure, contains lignin and polysaccharides. Under heat source conditions, the active groups (such as phenolic hydroxyl and methoxy groups) in the lignin molecules and the hydroxyl groups in the polysaccharides undergo a series of complex chemical reactions, forming chemical bonds and achieving material adhesion and cross-linking. This cross-linking effect ensures that the fibers are not merely physically entangled but tightly connected by covalent bonds, forming a relatively stable overall structure. Combined with the thickness uniformity data, it can be seen that the single-layer and multi-layer matrix blocks prepared in Examples 1-3 have better thickness uniformity than those in Comparative Examples 1-3, with the multi-layer matrix blocks exhibiting better thickness uniformity than the single-layer blocks. After pretreatment with a fiber dissociation accelerator, the fiber size becomes more uniform. This is because the dissociation accelerator can control the degree of fiber dissociation, preventing some fibers from being too thick or too thin. Uniform fiber size allows for better filling of space during subsequent weaving and molding, forming a denser and more uniform structure. Compared to a single layer, the multi-layer structure further increases the complexity and layering of fiber weaving, resulting in more uniform stress distribution and lower thickness dispersion. Appropriate tensile and flexural strength of the substrate block is crucial for its ability to withstand external forces and reduce breakage during subsequent processing, handling, and long-distance transportation. Thickness uniformity and good water absorption rate are well-suited for use in seedling production lines, improving seedling efficiency and quality. Data on the 1-second and 3-second water absorption rates of the substrate blocks show that the water absorption rate of the dry-prepared multi-layer substrate blocks is relatively lower than that of the single-layer substrate blocks. This is because the bottom and middle layers of the multi-layer substrate blocks contain a portion of a highly active, dark brown liquid derived from straw, which to some extent reduces the product's water absorption rate, but the difference is not significant. Furthermore, the water absorption rate of the substrate blocks prepared by adding a dissociation promoter to the composite modified straw fiber was higher than that of the control group, which further indicates that the improvement of this technical solution can effectively improve the water absorption of the substrate blocks, which is conducive to solving the practical problems encountered by the team in the early promotion of agricultural products, such as slow water absorption, low seedling quality, and the impact on rice seedling quality.
[0077] The two types of substrate blocks, WSSB-III and DSSB-III, from Examples 5 and 6 were compared with the straw substrate blocks (PTSSB) prepared by the team's previous technology (the preparation method is described in the literature "Yong Cheng, et al. Effect of straw fiber size on drying and water absorption rate of seedling substrate blocks [J]. Chinese Agricultural Science Bulletin, 2024, 40(15): 143-150.") under normal temperature conditions for 90 s dynamic changes in water absorption rate. The results are as follows: Figure 4 As shown, the DSSB-Ⅲ and WSSB-Ⅲ prepared by this technical solution have a faster water absorption rate in the initial stage (first 20 s), quickly reaching a high water absorption rate in a short period of time, after which the rate gradually slows down and eventually stabilizes. In contrast, the water absorption rate of PTSSB is slower in the initial stage, and the final water absorption rate is also lower than that of DSSB-Ⅲ and WSSB-Ⅲ. This indicates that the DSSB-Ⅲ and WSSB-Ⅲ prepared by the embodiment have stronger water absorption capacity, can quickly absorb and retain more moisture, and thus prove that the substrate blocks prepared by this embodiment can effectively improve the water absorption efficiency of the substrate blocks in the seedling production line process, laying a good, safe and stable wet environment for the subsequent dark seed germination.
[0078] Figure 5 The results show the changes in surface contact angles of WSSB-Ⅲ, DSSB-Ⅲ, and PTSSB. The contact angle directly reflects the water absorption of the substrate block surface. It can be seen that the contact angles of WSSB-Ⅲ and DSSB-Ⅲ are significantly lower than those of PTSSB. The contact angles decreased from the initial 87.21°, 78.69°, and 102.08° to 45.67°, 34.99°, and 98.93°, respectively. The contact angle decreases of WSSB-Ⅲ and DSSB-Ⅲ reached 47.63% and 55.53%, respectively, while that of PTSSB decreased by only 3.01%.
[0079] Figure 6 The images show the changes in water absorption of the two substrate blocks over a period of 1–5 seconds. They clearly demonstrate that the surface water absorption of WSSB-Ⅲ is significantly higher than that of PTSSB, indicating that the substrate blocks prepared using this technology can significantly improve the water absorption performance of the product. In summary, compared to PTSSB, WSSB-Ⅲ and DSSB-Ⅲ are more conducive to automated seedling production lines, effectively solving the problem of poor hydrophilicity in substrate blocks prepared using traditional techniques.
[0080] In addition, to verify the effect of the substrate blocks prepared in this technical solution on the quality of rice seedling population, Table 4 shows the seedling quality of WSSB-Ⅲ, DSSB-Ⅲ and PTSSB at 20 days of rice seedling raising.
[0081] Table 4. Seedling quality of WSSB-III, DSSB-III, and PTSSB at 20 days of rice seedling raising.
[0082] As shown in Table 4, compared with PTSSB, the use of WSSB-III and DSSB-III can significantly improve the overall quality of rice seedlings, with the seedling vigor index increasing from 0.0133 to 0.0143-0.0149. Among these improvements, the stem base width increased by 1.81%-3.01%, and the underground dry weight per 100 plants increased by 6.15%-10.77%. Root cohesion increased by 9.00%-21.09%.
[0083] Figure 7 Comparing the root system diagrams of WSSB-Ⅲ and PTSSB rice seedlings, it can be seen that the roots of WSSB-Ⅲ are whiter, the root system is more tightly interwoven, and the root quality is better. Figure 8 Based on their corresponding root vigor, it is evident that WSSB-Ⅲ has stronger root development than PTSSB, indicating that the embodiment can provide more nutrients and a suitable environment to promote seedling growth. In particular, the increase in stem base width indicates improved lodging resistance. The substrate block prepared by the composite modified straw fiber formed by catalytic dissociation pretreatment can promote the photosynthesis of seedlings and the effective absorption of nutrients by the roots, providing a material basis and guarantee for subsequent growth.
[0084] Meanwhile, the root vigor of rice seedlings was measured by WSSB-Ⅲ, DSSB-Ⅲ and PTSSB at 20 d, 30 d and 35 d of rice seedling raising, respectively. The test results are shown in Table 5.
[0085] Table 5. Seedling root activity of WSSB-III, DSSB-III and PTSSB
[0086] Root activity was measured using the α-naphthylamine method, as detailed in the literature “Ramasamy S, et al. Yield formation in rice in response to drainage and nitrogen application[J]. Field Crops Research. 1997, 51(1-2): 65-82.”.
[0087] Table 5 shows that the root activity of seedlings from WSSB-III, DSSB-III, and PTSSB substrate blocks all increased with the extension of seedling raising time. Furthermore, the root activity of WSSB-III and DSSB-III at 35 days was 14.67%–19.02% higher than that of PTSSB, indicating that WSSB-III and DSSB-III can effectively improve root physiological activity, possibly due to their favorable pore structure and slow-release nutrient properties. These results also demonstrate that the substrate blocks of this technical solution can effectively delay root senescence, and have significant practical value for cultivating robust seedlings of appropriate age.
[0088] Further comparisons were made between WSSB-Ⅲ, CK-WSSB-Ⅲ, DSSB-Ⅲ, CK-DSSB-Ⅲ, and PTSSB, as well as the matrix block prepared in Example 4 according to the method in Example 5, and the total phenolic acid content was determined. See Table 6 for details.
[0089] Table 6. Phenolic acid content of straw substrate blocks PTSSB WSSB-Ⅲ CK-WSSB-Ⅲ DSSB-Ⅲ CK-DSSB-Ⅲ Example 4A Matrix Block <![CDATA[Total phenolic acid content / (μg·g -1 )]]> 146.61 67.56 105.34 83.61 116.09 85.94 The total phenolic acid content was determined by the Folin-Ciocalteu method, as detailed in the literature: "Wu E, et al. Determination of total phenolic acid content in soil by phosphomolybdic acid-phosphotungstate colorimetric method [J]. Environmental Chemistry, 2000, 19(1): 67-72.
[0090] Table 6 shows that the total phenolic acid content of WSSB-Ⅲ and DSSB-Ⅲ was significantly lower than that of PTSSB, with reductions of 55.82% and 42.97%, respectively. Even CK-WSSB-Ⅲ and CK-DSSB-Ⅲ, prepared using steam pretreatment without catalyst addition, still had a total phenolic acid content approximately 20.82%–28.15% lower than PTSSB. This indicates that the total phenolic acid content of the matrix blocks prepared using either dry or wet molding methods was significantly lower than that of PTSSB prepared using bio-fermentation techniques. Adding a decomposition promoter during pretreatment further significantly reduced the total phenolic acid content. The reason for this is that during the straw segment pretreatment, cerium and zinc oxides with enzyme-like effects adhered to the straw segments. These substances have a certain decomposition and transformation effect on the phenolic acid monomers produced by lignin depolymerization, resulting in a lower total phenolic acid content in the matrix blocks, which is beneficial for seed germination and growth. This result can also be verified in Table 3. Compared with WSSB-Ⅲ, the matrix block of Example 4 had a 27.21% higher total phenolic acid content, indicating that the addition of dissociation aids during the straw segment pretreatment process plays an important role in promoting the dissociation system and can significantly degrade the total phenolic acid content in the product.
[0091] Furthermore, the sugar composition and proportion of the dark brown liquid with high activity of straw macromolecular structure produced simultaneously in Examples 1-3 and Comparative Examples 1-3 were detected, and the results are shown in Table 7.
[0092] Table 7. Polysaccharide components and their proportions in the dark brown liquid system
[0093] Determination of polysaccharide components in dark brown liquid system: After filtration through a 0.22 μm filter membrane and dilution by 10 times, the sugar composition and content were determined by liquid chromatography.
[0094] Based on the test results in Table 7, the polysaccharide component in the dark brown liquid system mainly consists of xylose, glucose, cellodimethylamine, and arabinose. Xylose and glucose are the main components, being the dissociation products of hemicellulose and cellulose during the processing, respectively. Furthermore, the hemicellulose sugar content in the example was higher than that in the comparative example, indicating that adding metal salts to the dissociation system can enhance the dissociation of hemicellulose, thereby increasing the looseness of straw cellulose and improving the dimensional stability of subsequent fiber-molded products.
[0095] In addition, the main substances and contents of phenolic acids in the dark brown liquid system were detected, and the results are as follows: Figure 9 As shown. Phenolic acids mainly include 4-hydroxybenzoic acid, vanillic acid, syringic acid, vanillin, p-coumaric acid, syringin, and trans-ferulic acid, which are the main products of straw lignin depolymerization. Among them, p-coumaric acid and trans-ferulic acid are the main products. Moreover, the contents of p-coumaric acid and trans-ferulic acid in the depolymerization products of Examples 1-3 are higher than those in Comparative Examples 1-3, indicating that the depolymerizing agent system has a promoting effect on straw lignin and can improve the solubility of the products in the liquid phase, thereby relatively reducing the deposition of lignin depolymerization products on the surface of the dissociated fibers.
[0096] Simultaneously, the dark brown liquid was diluted to 1‰ and applied to rice seedling cultivation. It was sprayed on the leaves 6 days after the rice seedlings were cultivated. After spraying, the rice leaves turned significantly greener. On the 10th day, the enzyme activity and chlorophyll content of the aboveground parts of the seedlings were measured. See Table 8 for details.
[0097] Table 8 Effects of co-production liquid on superoxide dismutase (SOD) and chlorophyll in rice seedlings Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 SOD activity (U / g fresh weight) 1454.62 1343.93 1398.54 1254.32 1167.44 1221.68 Chlorophyll SPAD 24.35 23.08 23.27 22.92 21.68 22.14 Superoxide dismutase (SOD) assay method: Reference "Wu Xiang, et al. Effects of 2,4-epibrassinolide on root growth and physiological characteristics of rice seedlings raised on biochar substrate [J]. Chinese Journal of Rice Science, 2024, 38(06): 685-694.
[0098] SPAD was measured using a Konica Minolta SPAD-502 handheld portable chlorophyll meter from Japan, measuring the SPAD of the top leaf of rice.
[0099] Analysis of the data in Table 8 shows that the dark brown liquid with high activity of the straw-derived macromolecular structure obtained from the co-production of Examples 1-3 showed an improving effect on the superoxide dismutase (SOD) activity and chlorophyll content of rice seedlings compared with Comparative Examples 1-3, with corresponding increases of 14.48%-15.97% and 5.10%-6.46%, respectively. This is mainly because cerium and zinc salts were introduced during the early straw segment treatment in Examples 1-3. These cerium and zinc salts can be converted into cerium and zinc oxides with enzyme-like effects during the steam pretreatment of straw segments. The catalytic substances that promote the formation of the dissociation agent system and the synergistic effect of the dissociation aid can simulate the functions of SOD and catalase, directly scavenging superoxide anion free radicals (O2⁻·) and hydrogen peroxide (H2O2), thereby reducing oxidative stress and protecting the integrity of cell membranes and organelles. Furthermore, after the straw segments are catalytically dissociated, the three cellulose elements of the straw, especially hemicellulose and lignin, will depolymerize into substances such as phenols and sugars. These substances are squeezed out and left in a dark brown liquid, which can be used as an effective multifunctional foliar fertilizer to promote the photosynthetic efficiency and growth of rice.
[0100] The above description represents the preferred embodiments of the present invention. Commonly known technical solutions and / or characteristics are not described in detail here. It should be noted that those skilled in the art can make various improvements and modifications without departing from the principles of the present invention. Such improvements and modifications should also be considered within the scope of protection of the present invention, and will not affect the effectiveness of the invention or the practicality, inventiveness, or innovativeness of the patent. The scope of protection claimed in this application should be determined by the content of its claims, and the specific embodiments described in the specification can be used to interpret the content of the claims.
Claims
1. A highly absorbent, multifunctional composite modified straw fiber, characterized in that, The composite modified straw fiber is prepared by the following method: S1: Mix choline chloride and formic acid in equal proportions to obtain a eutectic solvent and heat it to a molten state. Then add it to water at 75~80℃, and then add eugenol. Stir thoroughly to prepare a solution with a mass fraction of 0.1~0.5%, which is the dissociation aid. Add metal salt to the dissociation aid and mix well to obtain the dissociation promoter system. The mass ratio of eugenol to the eutectic solvent added is 1:2; The metal salt is obtained by mixing zinc salt and cerium salt in a molar mass ratio of (0~1):1; S2: Add straw segments and sedimentation promoter to the dissociation promoter system, and soak for 3~12 h to obtain high-moisture pretreated straw segments with a moisture content of 75~95%; The precipitation promoter is at least one of urea or ammonia water; The mass ratio of added straw segments, dissociation aid, metal salt, and precipitation promoter is 100:(0.1~0.5):(0.01~0.1):(0.1~0.5). S3: Place the high-moisture pretreated straw segments obtained in step S2 into a steam treatment at 100~120℃ for 30~120 min to obtain highly absorbent modified straw segments; S4: Add citric acid solution to the highly absorbent modified straw segments obtained in step S3, and mechanically decompose and separate the fibers using a twin-screw extruder or a single-axis tearing and spinning machine to co-produce a dark brown liquid, thereby obtaining the highly absorbent, multifunctional composite modified straw fiber.
2. The highly absorbent, multifunctional composite modified straw fiber according to claim 1, characterized in that, The straw includes at least one of the following: rice, wheat, corn, cotton stalks, bamboo, reeds, sorghum, hemp stalks, sugarcane bagasse, and agricultural and forestry waste straw.
3. The highly absorbent, multifunctional composite modified straw fiber according to claim 1, characterized in that, The metal salt is obtained by mixing zinc salt and cerium salt in a molar mass ratio of (0.5~1):
1.
4. The highly absorbent, multifunctional composite modified straw fiber according to claim 1, characterized in that, The zinc salt is zinc chloride; the cerium salt is one or more of cerium chloride, cerium nitrate, or cerium sulfate.
5. The highly absorbent, multifunctional composite modified straw fiber according to claim 1, characterized in that, The steam treatment refers to placing high-humidity pretreated straw segments on several layers of stainless steel steam plates, and then placing them in a cooking tank for hydrothermal treatment.
6. The highly absorbent, multifunctional composite modified straw fiber according to claim 5, characterized in that, The steaming plate is a stainless steel plate with circular holes of 0.3~0.5 cm in diameter and a hole spacing of 3 cm.
7. The highly absorbent, multifunctional composite modified straw fiber according to claim 5, characterized in that, The aforementioned layers are 1 to 4 layers.
8. A single-layer matrix block, characterized in that, The matrix block is obtained by filtration molding of the composite modified straw fiber described in any one of claims 1-5.
9. A multilayer matrix block, characterized in that, The multi-layer matrix block is obtained by hot pressing after being laid out in a discrete interlaced manner with upper fiber, middle fiber and lower fiber; the upper fiber is any of the composite modified straw fiber described in claims 1-5; the lower fiber is obtained by homogenizing the composite modified straw fiber described in claims 1-5 with the dark brown liquid; the middle fiber is obtained by mixing the composite modified straw fiber described in claims 1-5 with the lower fiber in an equal proportion.
10. The multilayer matrix block according to claim 9, characterized in that, In the lower layer of fiber, the volume-to-mass ratio of the dark brown liquid to the composite modified straw fiber is 5%, and the volume-to-mass ratio is expressed in ml / mg.
Citation Information
Patent Citations
Multilayer straw substrate for rice hole tray dry nursery seedling and preparation method and application thereof
CN109362533A
Preparation method and application of total-nutrient degradable straw seedling culture substrate block
CN110692489A
Method for dissociating plant fiber secondary wall S2 layer
CN112941947A
